2018
DOI: 10.1016/j.bbmt.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Engagement with INSPIRE, an Online Program for Hematopoietic Cell Transplantation Survivors

Abstract: In a secondary analysis of a randomized controlled trial (RCT), we examined participants' engagement with INSPIRE, a personalized online program for hematopoietic cell transplantation (HCT) survivors that focuses on cancer-related distress, depression, fatigue, and health care needs. We approached all adult, 3- to 18-year HCT survivors treated for hematologic malignancy without relapse or second cancer in the previous 2 years for participation in an RCT with either immediate or delayed access to INSPIRE. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The original screening yielded 22 selected articles. One paper 23 reported the engagement outcomes of a study whose main outcomes were reported elsewhere, 24 and the decision was to include it as well. Therefore, a total of 23 papers 23 45 representing 17 unique studies were included in this review ( Appendix 2 ; see Additional Files).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original screening yielded 22 selected articles. One paper 23 reported the engagement outcomes of a study whose main outcomes were reported elsewhere, 24 and the decision was to include it as well. Therefore, a total of 23 papers 23 45 representing 17 unique studies were included in this review ( Appendix 2 ; see Additional Files).…”
Section: Resultsmentioning
confidence: 99%
“…One paper 23 reported the engagement outcomes of a study whose main outcomes were reported elsewhere, 24 and the decision was to include it as well. Therefore, a total of 23 papers 23 45 representing 17 unique studies were included in this review ( Appendix 2 ; see Additional Files). Appendix 2 contains the summarized details of each of the 17 unique studies in these categories: study design, cancer population, symptoms, connected cancer symptom management system, feasibility, and key study impact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survivors of a hematologic malignancy who were between 3 and 18 years post‐HSCT, able to communicate and complete patient‐reported outcome (PRO) measures in English, and with internet and email access were recruited from a single transplant center for the INSPIRE randomized controlled trial [NCT00799461] 18,19 . The Fred Hutchinson Cancer Research Center Institutional Review Board approved the trial.…”
Section: Methodsmentioning
confidence: 99%
“…In a multi-center prospective, randomized control trial (RCT), it was effective in reducing cancer and treatment distress and improved the mental health domain of quality of life [13]. An internet-based intervention, INSPIRE (INternet-based Survivorship Program with Information and Resources), was also tested in an RCT, and had a marginal benefit in alleviating distress in an intent-to-treat analysis, although a significant effect on relieving distress in those who logged into the program [15,16]. In an effort to further improve upon the out-comes of these two approaches, we are combining the individualized mailed SCPs and the INSPIRE intervention in an online health program with an interactive, individualized mobile app and website.…”
Section: Introductionmentioning
confidence: 99%